2011
DOI: 10.1038/nm.2391
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an innate T helper type 17 response to intestinal bacterial pathogens

Abstract: Interleukin 17 (IL-17) is a central cytokine implicated in inflammation and antimicrobial defense. After infection, both innate and adaptive IL-17 responses have been reported, but the type of cells involved in innate IL-17 induction, as well as their contribution to in vivo responses, are poorly understood. Here we found that Citrobacter and Salmonella infection triggered early IL-17 production, which was crucial for host defense and was mediated by CD4(+) T helper cells. Enteric innate T helper type 17 (iT(H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
205
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 214 publications
(229 citation statements)
references
References 42 publications
21
205
1
1
Order By: Relevance
“…The kinetics at which MHCII −/− →WT mice succumbed to the infection, with the first animal dying as early as 3 days p.i., further suggests that CD4 + T cells play a critical protective role in the early phases of infection with C. rodentium in the chimeras. We previously found that the intestinal microbiota was essential for the generation of an iTh17 response to an enteric bacterial pathogen, as this response was completely blunted in germ-free mice infected with Salmonella Typhimurium [23]. Here, we now provide evidence that MHCII is also required for the induction of early lamina propria Th17 responses to bacterial infection, which strongly suggests that specific antigens are needed to either prime or drive this response.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The kinetics at which MHCII −/− →WT mice succumbed to the infection, with the first animal dying as early as 3 days p.i., further suggests that CD4 + T cells play a critical protective role in the early phases of infection with C. rodentium in the chimeras. We previously found that the intestinal microbiota was essential for the generation of an iTh17 response to an enteric bacterial pathogen, as this response was completely blunted in germ-free mice infected with Salmonella Typhimurium [23]. Here, we now provide evidence that MHCII is also required for the induction of early lamina propria Th17 responses to bacterial infection, which strongly suggests that specific antigens are needed to either prime or drive this response.…”
Section: Discussionsupporting
confidence: 58%
“…In particular, it is unclear if specific pathogenderived and/or microbiota-derived antigens are required to prime Th17 cells. In vitro studies suggest that the induction of a specific network of cytokines is sufficient for the activation of these cells [26]; however, our previous study identified a crucial role for the intestinal microbiota in promoting innate Th17 responses in the cecum of Salmonella-infected mice [23]. This suggests a key role for specific antigens in iTh17 induction in the intestine following bacterial infection.…”
Section: Introductionmentioning
confidence: 85%
“…Thus, stimulation of human dendritic cells (DCs) with MDP has been shown to enhance NOD2-mediated production of IL-1β and IL-23 which in turn promotes IL-17 production by memory Th17 cells [64]. Moreover, a recently study reported by Geddes et al [65] suggests a specific role for NOD2 in the early innate response. The authors used a mouse model in identifying an early NOD2-dependent Th17 response restricted to the acute phase of infections after treatment with pathogens, including Salmonella Typhimurium and Citrobacter rodentium.…”
Section: The Mdp-nod2 Pathway and T Helper Cell Regulationmentioning
confidence: 99%
“…The authors used a mouse model in identifying an early NOD2-dependent Th17 response restricted to the acute phase of infections after treatment with pathogens, including Salmonella Typhimurium and Citrobacter rodentium. NOD2 expression by myeloid and somatic cells was a crucial factor in recognition of pathogens and thereby for a functional early Th17 response [65]. Further, impaired acute Th17 responses in Nod2 knockout mice were associated with unaffected colonic colonization and diminished colonic inflammation at early stages, which is in contrast to an enhanced tissue destruction and increased bacterial translocation later in the course of the disease, indicating a protective role of the acute Th17 response in infection control [65].…”
Section: The Mdp-nod2 Pathway and T Helper Cell Regulationmentioning
confidence: 99%
See 1 more Smart Citation